(untitled) (Research, Society and Development, 2020)
This essay aims to contribute directly or indirectly to the study of controversies present in economic science. Situated in the context of the "COVID-19" pandemic, we seek to map and analyze the main economic policy positions and proposals present in the Brazilian public debate to confront the problem, identifying the possible theoretical foundations behind them. The methodological strategy was based on the analysis of the content and systematization of the positions raised in a time interval from March 15th to July 15th, 2020. It is assumed that state intervention is necessary and that there is an ideological and theoretical-methodological component embedded in policy recommendations. The main conclusion is a clear divide among economists who advocate a systematic intervention program against those who only recommend exceptional intervention. It is clear that disagreements and controversies among experts are less related to the "hits and misses" of economic policy itself, but largely influenced by the various foundations and assumptions they bring with them in their educational background and trajectory.